Cyprus Animation Association (CAA) - (:unkn) unknown (My University, 2026)
Cyprus Animation Association (CAA) is a local association which aims to represent professionals and artists in the disciplines of animation, motion graphics and visual effects. The association represents the International Animated Film Association ASIFA (Association Internationale du Film d’Animation) in Cyprus, and is a member of the Federation of Animation Producers Associations (Animation in Europe) and the Anna Lindh Foundation (ALF).